Avaliação das condições de qualidade em serviços de alimentação e unidades hospitalares na cidade Santa Maria - RS - Stangarlin, Lize (2009)
The aim of this work was to evaluate the conditions of quality of the establishments which produce food in Santa Maria. The present study was realized in ten food services of food (commercial and industrial) and five hospital nutrition units of Santa Maria (RS), in the months from April to July, in 2008. It was applied a specific list of evaluation from Good Practices in the food services and a list in the hospital units. It was realized swabs collection in the hands of the manipulators and in the surfaces after the cleaning up to verify the presence of positive Staphylococus coagulase and the total enumeration of the aerobic mesofilic microorganisms. It was applied a questionnaire to all food manipulators to verify their profiles and a questionnaire to fifty (50) clients and/or patients to each establishment to investigate the level of their satisfaction. It was observed a little consciousness and commitment from the establishments to the requisites required for the legislation to Good Practices. The microbiological analyses showed the low efficiency in the sanitation procedures of. The manpower employed is mainly female with commonness young manipulators who have regular scholar, receive their salaries according to their function. Work in average thirty hours a week and are satisfied with their timetable and the function they have. The majority employees work from 1 to 2 years in the establishments, try to keep their hand hygienic habits and half of the interviewee reported they had received a trainee in Good Practices. The clients and/ or the patients demonstrated to be satisfied with the quality of the taken services which every evaluated services were classified between Excellent and Good. According to what was exposed it is evident the necessity of the improvement of the hygienic-sanitary conditions and greater supervision from the competent parts and bigger investments in the periodic trainees to the food manipulators to make them to become conscious and able to the improvement of the procedures.